Development of an Economic Empowerment Framework for Small-scale Agro-processors in South Africa - (:unkn) unknown (My University, 2022)
Any nation that seeks sustainable economic growth and development must ensure the economic empowerment of its entire population. The aim of this study was to create an economic empowerment framework for the management of small-scale agro-processors in South Africa. Agriculture's position and function are evolving globally, and the agro- processing sector is no exception. Since 1994, strategies to fill policy gaps and build an ecosystem for small-scale agro-processors to fully engage in the formal economy have not yielded the desired results. However, creating an effective small-scale agro-processing sector is dependent on government programs to drive the process. While there is a policy (the South African Agri-BEE Transformation Charter), the framework is not clear. Its execution has not properly resolved the challenges of small-scale agro-processors in engaging in the formal economy, which is a perennial problem.Despite the South African government's significant investments in all areas to close gaps in the agro-processing market, the dominance of a few large-scale commercial enterprises is expanding. The central argument of this study is whether post-apartheid South Africa's government policies have modified the inherited agro-processing system to enable small-scale agro-processors to join the formal economy. The question is whether the existence of the previous agro-processing system is due to the government's failure to establish an empowerment mechanism capable of effectively addressing past inequalities in South Africa's agro-processing field. The thesis employs a mixed-method approach, with data gathered from small-scale agro-processors in five South African provinces.The data was analyzed using inferential (correlation analysis, hierarchical multiple linear regression analysis, multiple linear regression analysis, one-way factorial ANOVA, and structural equation modelling) and descriptive statistical techniques. The study discovered that the ne
Keywords: African Research